KAJIAN LITERATUR DESAIN PERPUSTAKAAN RAMAH DISABILITAS - Amalia Azka Rahmayani (Program Studi Ilmu Perpustakaan, Fakultas Adab dan Ilmu Budaya, UIN Sunan Kalijaga Yogyaka, 2020)
The library is one of the places frequented by visitors with the aim of learning, reading, doing research, communicating and building relationships with others. Visitors who was came to the library come from a variety background. Ranging from children to the elderly, even from various regions and countries, and visitors with special needs or disabilities. Therefore, the function of the library as a learning tool must be able to serve various kinds of visitors so that it can be used as much as possible. To be able to serve a variety of visitor populations, especially for disabilities, adequate design is required. Like its design, its services, existing facilities, and library collections must be able to accommodate all visitors. Several studies have conducted to evaluate disability-friendly libraries. So that, this literature review journal conducted to collect and discuss previous research related to library evaluations in various disability-friendly places. In addition, researchers will also make a comparison of several library designs to its weaknesses and strengths they have to accommodate all visitor populations, especially for disabilities.Keywords: library, disability, service, facility